Factor structure of the Jefferson Scale for Empathy among medical undergraduates from South India - Samir Kumar Praharaj; Santosh Salagre; Podila Sathya Venkata Narasimha Sharma (Indian Journal of Psychiatry)
Background: Empathy is a multidimensional construct and is considered an essential attribute among healthcare professionals. The Jefferson Scale for Empathy (JSE) is a commonly used tool to measure physician empathy and has been used in medical students as well; however, the psychometric properties have not been well studied in India. We aimed to study the factor structure of JSE among medical undergraduates. Methods: This was a secondary analysis of baseline data obtained from the Stigma, Empathy and Attitude module study among medical undergraduates (N = 157). The scores obtained on the 20-item JSE Medical Student Version were subjected to principal component analysis with varimax rotation. Eigenvalues greater than unity, scree plot, and Horn’s parallel analysis were used for identifying the factors. Items with loading more than 0.4 were included based on Steven’s recommendation. Results: The sample was adequate for factor analysis (Kaiser–Meyer–Olkin (KMO) measure 0.832). Five factors were extracted using principal component analysis, which explained 60% of the variance. The first three appeared as stable factors, and the last two factors had two items each. The first factor was the strongest (explained 18.8% of variance) with loadings from nine items. The second factor (explained 15.6% of variance) had loadings from six items, and two of the items showed correlation with the first factor. Conclusions: JSE has a multidimensional structure with five factors in our sample of medical undergraduates.